Problems on learning thinking aloud for reading via Zoom app in emergency remote learning class - Wijayanti, Anita; Gunawan, Yohanes Bambang (Journal of English Language and Pedagogy, 2021)
This research attempted to obtain information on the problems of learning think-aloud for reading in an emergency remote learning class utilizing Zoom video conference application as the means of communication. While think-aloud is well-known method for improving students' reading strategy usage management, there are still problems encountered during class, especially if it is learnt via Zoom video conference application. The research participants were nine D3 program students of AMIKOM Purwokerto University PSDKU Yogyakarta who took Reading IV class. Data collection procedure included literary research, observation, questionnaire, and group interview. There were seven problems discovered: (1) Students were too shy to talk, (2) Students did not have or know proper vocabulary to verbalize their thoughts. (3). Students understood the text but had nothing to say. (4) Easy text did not invoke observable understanding processes in the students’ minds. (5) Students neither understood the text nor knew what to say. (6) Time-consuming. (7) Internet disconnection. Simple solutions to those problems were also presented.